Umur Simpan Saos Tomat Pada Berbagai Konsentrasi Bahan Pengental - Catur Budi Handayani; A. Intan Niken Tari; Afriyanti Afriyanti (AGRISAINTIFIKA: Jurnal Ilmu-Ilmu Pertanian, 2018)
Research on the shelf life of tomato sauce at various coagulant concentrations uses local tomatoes from the Sukoharjo with a concentration of 5, 7.5 and 10% of maezena flour from tomatoes used. The shelf life calculation uses the Archenius method with storage for 4 weeks at 3 different temperatures namely refrigerator temperature (4 OC), room temperature (27 OC), and temperature of 50 OC. Calculations are based on changes in water content, fungal growth and organoleptic tests of taste. The calculation results show that the shortest shelf life of tomato sauce is 24 days for sauces with 5 and 7.5% coagulant and 47 days for sauces with 10% coagulant, which are calculated based on organoleptic test of taste.Keywords: tomato sauce, shelf life, coagulant